Exploring Collaborative Civic Leadership Among Young Tunisians: Inviting Despair, Creating Hope. (10th January 2017) - Kincaid, Sarah McLewin
Abstract: This article explores how civically engaged youth in Tunisia are approaching collaboration with noncivically engaged youth to promote greater levels of civic participation. This article is based on qualitative research conducted in Tunis, Tunisia during the summer of 2015 with 16 youth, all under the age of 35. This article will explore youth attitudes regarding civic engagement and barriers to participation in postauthoritarian Tunisia. This article also explores how civically engaged youth utilize informal social spaces such as coffee shops, universities, and social media sites to stir a sense of hope and pride in activism. This research provides a rich snapshot of civically and noncivically engaged youth who comprise 51% of Tunisia's population and led the 2011 revolution that burgeoned the so‐called Arab Spring in North Africa and the Middle East. These findings bring into question labels such as "politically inactive" and "potential ISIS fighters" that are employed in the dominant narrative on Tunisian youth. Finally, this research suggests that Tunisian youth wield powerful leadership skills that will continue to play a critical role in the transformation of civic and social norms.